Method Effect VAKT (Visual, Auditory, Kinesthetic, Tactile) On Beginning Reading Ability and Writing Skills of Class I Students - Rosnaeni; Sulfasyah; Sitti Aidah Azis (IJER (Indonesian Journal of Educational Research), 2022)
This type of research is a Quasi Experimental Design with the research design that will be used is the nonequivalent Control Group Design, in this study a certain treatment is given, namely the control class and the experimental class. The number of samples in this study were 58 students. The data collection method used is the activity of learning to read the beginning of grade I students and writing skills tests and documentation. The data analysis technique used is the first by using a descriptive statistical approach, inferential statistics and manova hypothesis testing. The results showed that: 1) the activities of students in the experimental class using the VAKT method with a total score of 52 divided by the total score multiplied by one hundred with a total result of 81.25. From these results it can be concluded that the VAKT method can affect the ability to read at the beginning of class I; 2) the statistical test of the experimental class is 83.59 and getting a good classification score, it can be concluded that the use of the VAKT method can affect the initial writing skills of first grade students; and 3) test the Manova hypothesis with a significant value of 0.000 <0.05, it can be concluded that there is an effect of the VAKT method on students' reading and writing skills